Growth Performance and Histological Changes in Ileum and Immune Related Organs of Broilers Fed Organic Acids or Antibiotic Growth Promoter - Mohamed, M.A.; El-Daly, Eman F.; El-Azeem, Nafisa A. Abd; Youssef, Amani W.; Hassan, H.M.A. (International Journal of Poultry Science, 2014)
An experiment was designed to evaluate the effects of using organic acids as an alternative to antibiotic growth promoter on performance of broiler chicks. Carcass characteristics, histological changes of ileum and immune related organs (bursa, thymus and spleen) along with intestinal bacteria count were also studied. A number of 150 Cobb broiler chicks were fed on three dietary treatments: a basal corn-soybean meal diet served as a control treatment with no supplements or supplemented with either 0.025% Bacitracin Methylene Disalicylat (BMD, antibiotic) or 0.06% Galliacid® (organic acids) from 10 to 36 days of age. The results showed that birds fed antibiotic or organic acids gained significant (p